Thinking in systems: Problems of organization at the Center for Advanced Study in the Behavioral Sciences and the Society for General Systems Research, 1950–7 - O’Neil, Libby (History of the human sciences, 2025)
This article analyzes the approach to systems theory promoted by Ludwig von Bertalanffy and Kenneth Boulding during their time at the Ford Foundation’s Center for Advanced Study in the Behavioral Sciences (CASBS) in 1954–5 and in the pages of the 1956 General Systems Yearbook . At the Ford Foundation’s Center, social scientists engaged in interdisciplinary research on ‘problems of organization’ that encouraged them to develop theoretical tools that scaled between organisms, institutions, and social organizations. Bertalanffy and Boulding were able to gain financial support from the Center for their ‘general system(s) theory’ that promised to solve these ‘problems of organization’ while unifying the social sciences in the service of the Foundation’s philanthropic mission. Systems thinkers at the Center founded the Society for General Systems Research, an important professional organization for systems theory in the coming decades. In the Society’s General Systems Yearbook , Bertalanffy and Boulding debated the meaning and underlying politics of thinking in systems in language shaped by their time at CASBS. By attending to this instantiation of systems thinking in its institutional and social context, this article attempts to tell a history of system without accepting the universalizing aspirations of its historical subject.